Meningkatkan Kemampuan Literasi Sains Mahasiswa PGSD Unsar Melalui Model Pembelajaran Berbasis Masalah - Zulfah Rizka Purnama; Hermin Hermin; Syahrir Syahrir; Ida Sitti Hamidah; Nur Laely; Ina Tuto Tukan (P3M Politeknik Negeri Ambon, 2024)
Literacy is the ability to process and understand information when carrying out reading and writing activities. Students will gain very broad knowledge through literacy activities because they are closely related to critical thinking skills. To improve scientific literacy skills, besides requiring student motivation, educators also need to consider learning strategies that are appropriate to the conditions and potential of students, where the learning process focuses on providing direct experience and applying the essence of science. Literacy activities in higher education are carried out by utilizing various reference sources, applying literacy strategies in the learning process, and combining literacy strategies with problem solving activities. Literacy and critical thinking are very important for students, especially in the era of disruption which is experiencing very rapid developments in science and technology. Thus, this article aims to analyze the role of literacy in improving critical thinking skills and implementing a literacy culture in higher education. The research method used is the classroom action research method (PTK) which requires collaboration between lecturers and students. Keywords: Literacy